Pengaruh kecerdasan adversitas dan kecerdasan emosional melalui model inkuiri sosial terhadap keterampilan sosial siswa - Wardani Wardani (Jurnal Teori dan Praksis Pembelajaran IPS, 2019)
The research purpose is to know the effect of adversity intelligence and emotional intelligence through social inquiry models against social skills. The research method used ex post facto — the collection data technique using questionnaires. The taking sample technique is approached by simple random sampling.  The amount of sample is 104 students on SMP N 10 Bandar Lampung. The data analysis using Structural Equation Modeling (SEM). The research result shows that there are a definite relation linkages between endogenous variable, exogenous variable, and intervening variable. Through the social inquiry model, intelligence and emotional intelligence adversity will play a role effective in improved the skills of social. It would be useful for a student to are learning success in classes and the future. It is expected that schools can optimize emotional adversity intelligence and intelligence to enhance their social skills and skills students academics. It can be concluded that if adversity intelligence and emotional intelligence through social inquiry model against social skill.DOI: 10.17977/um022v4i22019p066